TRAINING FOR HOUSEHOLD WASTE INTO EFFECTIVE MATERIALS FOR COMMUNITIES RT06/16, TOMANG, JAKARTA BARAT - Fadliah, Fadliah; Dahani, Wiwik; Pratiwi, Reno; Subandrio; Aryanto, Reza; Kurniawati, Riskaviana (Universitas Trisakti, 2023)
The production process with the green synthesis method is a method that is being developed in the production process for daily household needs. One of the green synthesis methods that has been developed is using waste products such as waste cooking oil (WCO) as a raw material in the soap production process. In the process of making soap, saponification reactions occur between triglycerides and fats and oils that occur in alkaline solutions. The materials used are a mixture of WCO, distilled water, and sodium hydroxide. The WCO used in this training is purified WCO with the addition of natural zeolite. Acid-activated natural zeolite, to increase its catalytic ability, is used as an adsorbent to adsorb impurities contained in WCO. The training consists of three stages: providing material about the dangers and negative effects that can be caused by using used cooking oil in everyday life for both the environment and health, the WCO cleaning process, and the utilization of purified WCO into an efficient product in the form of laundry soap. The results of the activities carried out can be seen from the discussion activities carried out after the activity took place with the partner community, which show an increase in community knowledge about how to treat waste and the potential for improving the economic situation of the community through knowledge of the soap-making process.